Policy on Criminalisation of Necrophilia Behaviour: Case Study of Junior High School Students in Mojokerto - Isnawan, Fuadi (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
This tragic story involves a young man named M. Adi (19 years old) in Mojokerto, East Java, who was desperate to rape the corpse of junior high school student AE (15 years old). This incident occurred after his life was taken by his classmate, AB (15 years old). Adi raped AE's corpse twice, as the victim's life was taken by AB. Adi's motive was lust. The young man worked as a labourer in an iron factory, earning around Rp500,000 per week. This case began with AB's murder in the rice field behind his house. AB then took AE's body on a motorbike belonging to the victim's uncle to his parents' house. There, Adi was invited by AB to help dispose of AE's body. Adi raped the victim's body twice in an empty house. AB confessed his actions to the police and explained that Adi committed the rapes when he went to buy raffia rope to tie the plastic sack that would be used to wrap the victim's body. This case revealed a cruelty and perversion of behaviour that was deeply disturbing, and society and the law responded strongly to it. Corpse rape, or necrophilia, is a highly reprehensible act that goes against moral and ethical values. Involving sexual acts against a dead human body, which lacks the ability or awareness to consent or engage in the relationship, necrophilia violates basic human principles and social norms held by society. This case also highlights the lacunae in the law regarding necrophilia. While there is a threat of punishment for individuals who engage in corpse rape or mutilation, the existing arrangements have not been specific and explicit enough in addressing acts of necrophilia. Therefore, it is important to consider criminalising necrophilia more explicitly in order to address such inhumane acts and protect human dignity even after a person has passed away. This research applies the normative juridical legal research method to analyse the criminalisation policy of the act of intercourse with a corpse in the case of a junior high school student in Mojokerto, with reference to Criminal Law and Pancasila. A case approach is used in analysing the criminalisation policy of Necrophilia from the perspective of Criminal Law and Pancasila.